ANALYSIS OF THE STATE DOMESTIC GOVERNMENT BOND MARKET DURING THE FULL-SCALE WAR - SHYMANSKA, Oksana; TSIKHOTSKYI, Serhii (Scientific journal «World of Finance», 2026)
Вступ. Ринок облігацій внутрішньої державної позики (ОВДП) є важливою складовою вітчизняної фінансової системи, особливо в умовах війни, яка зумовила необхідність трансформації усіх сфер життя країни, зокрема в контексті забезпечення потреб обороноздатності, вирішення гуманітарних проблем та пошуку додаткових джерел фінансування. ОВДП стали ключовим інструментом мобілізації внутрішніх фінансових ресурсів, що сприяє зменшенню залежності від зовнішніх запозичень і підтримує макрофінансову стабільність.Мета – дослідити функціонування ринку ОВДП в Україні в умовах повномасштабної війни, проаналізувати його структурні трансформації, чинники попиту, а також вплив на фінансову стійкість та боргову безпеку держави.Результати. Під час аналізу ринку ОВДП в Україні в умовах повномасштабної війни виявлено його ключові структурні, інституційні та поведінкові трансформації. Встановлено, що в 2022–2025 рр. ринок ОВДП став головним інструментом фінансування дефіциту державного бюджету, забезпечуючи понад половину обсягів внутрішніх запозичень. Незважаючи на провідну роль банківського сектору, у структурі власників ОВДП відбулося суттєве зростання частки фізичних осіб та небанківських фінансових установ, що засвідчує зміцнення довіри до державних боргових інструментів. Хоча динаміка дохідності ОВДП за досліджуваний період відрізнялася строкатістю значень, однак, у підсумку, стабілізація їх прибутковості в межах 16–18% корелює зі зниженням макрофінансової напруги. Доведено, що ринок ОВДП в умовах війни виконує роль як фіскального, так і стабілізаційного механізму, сприяючи підтриманню фінансової стійкості держави й мобілізації внутрішніх ресурсів.Висновки. В умовах повномасштабної війни ринок ОВДП став одним із ключових елементів фінансової архітектури України, забезпечуючи критично важливі потреби бюджету, насамперед у сфері оборони та гуманітарної підтримки. Структурні трансформації ринку ОВДП в аспекті зростання залученості фізичних осіб та бізнесу відображають консолідацію суспільства навколо ідеї фінансової підтримки держави. Цифровізація інвестиційних процесів, патріотична складова та розширення доступу до фінансових інструментів є найбільш вагомими неціновими чинниками впливу на попит на ОВДП. Introduction. The domestic government bond market (DGBM) is a vital component of Ukraine’s financial system, especially under wartime conditions that have necessitated the transformation of all spheres of national life. This includes meeting defense needs, addressing humanitarian challenges, and identifying additional sources of funding. DGBMs have become a key instrument for mobilizing internal financial resources, reducing dependence on external borrowing, and supporting macro-financial stability.The purpose of the article is to conduct a comprehensive analysis of Ukraine’s DGBM under full-scale war conditions, identifying key development trends, structural transformations, demand determinants, and the impact on financial resilience and debt security.Results. The analysis revealed that, under conditions of full-scale war, key structural, institutional, and behavioral transformations occurred in the domestic government bond (DGB) market. It was established that during 2022-2025, the DGB market became the primary instrument for financing the state budget deficit, accounting for more than half of the volume of domestic borrowings. Despite the leading role of the banking sector, the ownership structure of DGBs has shown a significant increase in the share held by individuals and non-bank financial institutions, indicating a strengthening of trust in government debt instruments. Although the dynamics of DGB yields during the studied period were characterized by considerable variability, ultimately the stabilization of profitability within the range of 16-18% correlates with a reduction in macro-financial tension. It has been proven that, under wartime conditions, the DGB market performs both fiscal and stabilization functions, contributing to the maintenance of the state’s financial resilience and the mobilization of domestic resources.Conclusions. Under the conditions of full-scale war, the domestic government bond market has become a crucial element of the country’s financial architecture, ensuring the critical needs of the state budget, primarily in the areas of defense and humanitarian support. Structural transformations of the GDB market, particularly the increased involvement of individuals and businesses, reflect the consolidation of society around the idea of financial support for the state. The digitalization of investment processes, the patriotic dimension, and the expansion of access to financial instruments represent the most significant non-price factors influencing demand for DGBs.